Rogue State Behavior and Markets: The Financial Fallout of North Korean Nuclear Tests - Christos Kollias; Stephanos Papadamou (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
Financial markets react to major political events. The two nuclear tests conducted by North Korea in 2006 and 2009 were a sober confirmation of the nuclear weapon capacity of this state with the concomitant potential security threat this posed for the stability of the greater region. We examine how ten regional stock exchanges and currency markets reacted to this security development and these two specific events. The results, although not uniform across all countries and markets, revealed a greater adverse effect in the case of the second of the two tests. On the whole, the adverse effects on the stock exchanges were short lived.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: H56; G1; G14; 330; nuclear tests and financial markets; event studies; GARCH models; quantile regression